Examining the interplay of coaching leadership styles, motivation, and anxiety: Insights from Filipino university student-athletes - Malquisto, Ma. Patricia; Cabuquin, Jomar; Alfarero, Joel (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
The Philippines' passion for sports is deeply ingrained in its culture and is evident in its participation in major national and international sporting events. Hence, it is crucial to determine a coaching leadership style for cultivating a solid coach-athlete relationship and facilitating the growth and achievement of motivated athletes. This study generally examined the associations between coaching leadership styles, motivation, and anxiety among Filipino university student-athletes at a public state university in Leyte province, the Philippines. It utilized a quantitative approach, specifically a descriptive cross-sectional survey and correlational design with 108 student-athlete respondents. Results revealed a statistically significant but weak positive association (rs=0.304, p=0.001) between coaching leadership and student-athlete motivation, suggesting that athletes who perceive their coaches as effective leaders exhibit higher motivation levels. However, no significant association was found between coaching leadership and student-athletes' anxiety (rs=-0.026, p=0.793), nor between student-athletes' anxiety and motivation (rs=-0.157, p=0.106). These results emphasize the complexity of factors influencing anxiety, including performance pressure, competition intensity, or personal expectations. While no single leadership approach universally applies, a deep understanding of various coaching styles is crucial for cultivating an optimal coach-athlete relationship that enhances motivation and performance.